Influence of Lateral Growth on the Surface Pit Formation of GaN Heteroepitaxial Film Grown by MOCVD - Zhiyuan GAO; Xiaowei XUE; Huimin LI; Jiangjiang LI; Li MA; Wenrong WU; Deshu ZOU (Medžiagotyra, 2016)
This study made an attempt to understand and control the heteroepitaxial growth of GaN from the view of the essential behaviors of crystal growth. Through a comparison of the nonpolar, polar and semipolar GaN epitaxial film, the influence of lateral growth on the surface pit formation mechanism has been investigated. For a-plane GaN, the lateral growth velocities of the less inclined {20-21} and {11-22} facets are approaching to the velocity of {10-11} facet under high temperature, so that the surface pit was transformed from a triangular shape to a pentagonal one. For c-plane GaN, the size of the surface pit produced by screw dislocation is determined by the lateral growth of the pit facets. A slow lateral growth rate of the inclined facets {10-11} compared with the vertical growth rate of (0001) facet under low V/III ratio would enlarge the pit size. For (11-22) semipolar GaN, surface pit is rarely observed, because the vertical growth velocity of {11-22} plane is slow compared with the lateral growth rate of the inclined facets, such as {11-20} and (0001). DOI: http://dx.doi.org/10.5755/j01.ms.22.2.12931